Habitat use by juvenile lampreys (Geotria australis) in a large New Zealand river - D. J. Jellyman; G. J. Glova (New Zealand Journal of Marine and Freshwater Research, 2002)
Ammocoetes (larvae) of Geotria australis Gray, were sampled in a large South Island, New Zealand, river during summer to determine their distribution and habitat associations. Ammocoetes were widely distributed along the length of the river, being present at 66 of the 95 sites sampled. They ranged in density from 0 to 180 m –2 , and were associated with habitat type (mainly runs), overhead shade, and substrate features (depth or the proportion of fine sand). The amount of particulate organic matter was negatively correlated with ammocoete abundance.